Phase-Shifting Common-Path Polarization Self-Interferometry for Evaluating the Reconstruction of Holograms Displayed on a Phase-Only Display - Nabadda, Esther; García-Martínez, Pascuala; Sánchez-López, María del Mar; Moreno, Ignacio (Frontiers in Physics, 2022)
In this work we apply a phase-shifting interferometry (PSI) to evaluate the reconstruction of complex-valued holograms displayed onto a phase-only spatial light modulator (SLM). The interferometer is vibration-free since it uses a common-path polarization arrangement based on the SLM itself, which is used simultaneously to display the hologram and to apply the phase-shifting values. The change from the hologram display configuration to the interferometer configuration involves only a rotation of a polarizer. The continuous phase modulation provided by the SLM allows using PSI with arbitrary phase bias values. Several examples are demonstrated by generating different combinations of modes with an efficient on-axis hologram encoding technique.